Penonjolan Identiti Budaya Melayu Menerusi Aplikasi Batik dalam Pembuatan Bot Gentian Kaca (Fibreglass Boat) di Universiti Kuala Lumpur Malaysian Institute of Marine Engineering Technology (UniKL MIMET), Lumut, Perak: The Projection of Malay Cultural Identity through Batik Application in the Development of the Fibreglass Boat at Universiti Kuala Lumpur Malaysian Institute of Marine Engineering Technology (UniKL MIMET), Lumut, Perak - Aizat Khairi,; Shamsul Effendy Abdul Hamid,; Shaiful Bakri Ismail, (Wacana Seni Journal of Arts Discourse, 2018)
Batik is one of the cultural elements in traditional craftsmanship especially among the Malays in Malaysia and generally in Southeast Asia region. Typically, batik is done on fabric material such as cotton and made into clothing for men and women. In Malaysia, batik is not only worn by the Malays but also by the non-Malays because of the attractive design and its suitability when attending formal and informal events. However, cultural identity through the art of batik is seen only in clothes, adornments and accessories. Hence, a group of lecturers and students of University Kuala Lumpur Malaysian Institute of Marine Engineering Technology (UNIKL MIMET) have explored the application of batik in fibreglass boat building as an alternative way of showing and maintaining Malay cultural identity. The method of this study was conducted through the experimental prototype fibreglass boat construction made by combining batik fabrics through certain processes. As a result, the external form of fibreglass boat was covered with batik fabrics and had made this boat even more beautiful and attractive. The batik fibreglass boat has the potential to contribute to the tourism sector as a cruise boat that can attract local and foreign tourists due to its own uniqueness. In addition, it also helps to maintain and promote the cultural heritage of the Malays through batik handicraft, which is applied to the fibreglass boat in Malaysia.